2018
DOI: 10.2337/db17-1226
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Insulin Receptor Pathway and Glucose Metabolism by CD36 Signaling

Abstract: During reduced energy intake, skeletal muscle maintains homeostasis by rapidly suppressing insulin-stimulated glucose utilization. Loss of this adaptation is observed with deficiency of the fatty acid transporter CD36. A similar loss is also characteristic of the insulin-resistant state where CD36 is dysfunctional. To elucidate what links CD36 to muscle glucose utilization, we examined whether CD36 signaling might influence insulin action. First, we show that CD36 deletion specific to skeletal muscle reduces e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 50 publications
(57 reference statements)
6
68
0
Order By: Relevance
“…Moreover, we recently found that inhibition of extracellular CTSD activity reduced plasma insulin levels and hepatic lipids in rats with hepatic steatosis ( 18 ). Likewise, our group also previously observed that inhibiting CTSD activity via pepstatin A (an aspartic lysosomal enzymes inhibitor) reduces the gene expression of CD36 (a transporter of FFA) ( 23 ) that also mediates the suppression of FFA on insulin signaling ( 37 ). This data thereby suggests that CTSD activity is likely involved with insulin signaling via regulating FFA metabolic pathways (i.e., CD36 transporter).…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, we recently found that inhibition of extracellular CTSD activity reduced plasma insulin levels and hepatic lipids in rats with hepatic steatosis ( 18 ). Likewise, our group also previously observed that inhibiting CTSD activity via pepstatin A (an aspartic lysosomal enzymes inhibitor) reduces the gene expression of CD36 (a transporter of FFA) ( 23 ) that also mediates the suppression of FFA on insulin signaling ( 37 ). This data thereby suggests that CTSD activity is likely involved with insulin signaling via regulating FFA metabolic pathways (i.e., CD36 transporter).…”
Section: Discussionmentioning
confidence: 90%
“…ilar improvements in insulin action or glucose metabolism, and, instead, hearts from these mice had downregulated expression of some glucose uptake genes, opposite to what would be expected with reduced lipid uptake. These changes might reflect myocyte-autonomous actions of CD36 that regulate insulin signaling (45). These separate effects on parenchymal biology could explain the propensity to develop insulin resistance in humans with CD36 mutations (46).…”
Section: Discussionmentioning
confidence: 99%
“…CD36 interacts with the insulin receptor, thereby promoting tyrosine phosphorylation of the receptor by Fyn kinase and enhancing downstream signaling, causing glucose uptake and utilization. In contrast, the presence of saturated FAs, but not unsaturated FAs, inhibits CD36-Fyn-dependent phosphorylation of the insulin receptor [ 133 ]. Therefore, CD36 influence on muscle fuel choice between FA and glucose depends on the metabolic state.…”
Section: The Role Of Cd36 In the Pathogenesis Of Dmmentioning
confidence: 99%
“…Therefore, CD36 influence on muscle fuel choice between FA and glucose depends on the metabolic state. The dysregulation of the CD36-dependent pathways of FA and glucose metabolism in skeletal muscles, occurring in chronic excess of FA and DM, may reduce their ability to modulate FA, and glucose utilization depends on energy needs, which will result in lipid accumulation and insulin resistance [ 130 , 133 ].…”
Section: The Role Of Cd36 In the Pathogenesis Of Dmmentioning
confidence: 99%